Arriar o Butô em 7 Encruzilhadas: micropolíticas do corpo - Abel, Thiago (2023)
What happens when macumbeiros create a dance experience from Tatsumi Hijikata's restlessness? This thesis presents how the Núcleo Experimental de Butô, from its works on the field of creation, research, and education, proposes an interlocution between the knowledges and practices of Hijikata and the enchanted sciences of the macumbas. Insights are gained on how the thoughts and creations of this japanese artist offer strategies on the destabilization of control systems, domination, and extermination; as well as awareness and liberation of bodies and desires through dance, creating strategies for a life less governed by the neoliberal system, less groomed by colonialism, more critical about the orientalisms, esotericisms and racisms present in Latin American artistic making; raising a genuine life that ensures the physical and mental health of the entire collective, achieving autonomy and freedom. Those who dance butoh in Brazil, with an eye open to the political struggles proposed by Hijikata since the beginning of the movement, end up discovering powerful ingredients to temper the farofa that will be delivered at the crossroads: a very strong ebó capable of dismantling the necropolitics present here since 1500